Graphic symbol preferences of adults with disabilities in one non-profit foundation in Greece - Pampoulou, Eliada; Diamanti, Ioanna (My University, 2020)
Purpose: Graphic symbols, such as photographs, Makaton and Pics for PECS, are often used in the field of augmentative and alternative communication (AAC) to support people with complex communication disorders. However, there is little research focusing on the preferences of people with disabilities in terms of which type of graphic symbol they prefer to use for their communication interactions. The purpose of this paper is to investigate the symbol preferences of people with Autism Spectrum Disorder and those with intellectual disability. The research questions are as follows: Do people prefer coloured or black and white symbols? What type(s) of symbols do they prefer to use for their communication interactions? What type(s) of symbols do they consider more appropriate for children? What type(s) of symbols do they consider more appropriate for adults? Design/methodology/approach: A questionnaire with simple instructions was used to elicit the information from the participants. Through purposive sampling, 25 participants between the ages of 20 and 32 were selected. Twelve participants had been diagnosed with autism spectrum disorder, while the rest had mild or moderate intellectual disability. Findings: Most of the participants preferred coloured symbols. Of all the six types of symbols, they preferred to use photographs and considered these as being the most appropriate symbols for adults, whereas, for them, Talking Mats is better for children. Originality/value: It is vital that the voices of people with disabilities are heard and taken into account when services are to be provided.
Keywords: Autism spectrum disorder; Intellectual disability; Makaton symbols; Photographs; Pics for PECS symbols; Pictures; Preferences; Symbols; Talking mats symbols; Widgit symbols